2013
DOI: 10.1152/ajplung.00370.2012
|View full text |Cite
|
Sign up to set email alerts
|

Combustion derived ultrafine particles induce cytochromeP-450 expression in specific lung compartments in the developing neonatal and adult rat

Abstract: Vehicle exhaust is rich in polycyclic aromatic hydrocarbons (PAH) and can be a dominant contributor to ultrafine urban particulate matter (PM). Exposure to ultrafine PM is correlated with respiratory infections and asthmatic symptoms in young children. The lung undergoes substantial growth, alveolarization, and cellular maturation within the first years of life, which may be impacted by environmental pollutants such as PM. PAHs in PM can serve as ligands for the aryl hydrocarbon receptor (AhR) that induces exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Cell populations are location-specific and have unique functions within the lung. The inability of neonates to upregulate antioxidants in the parenchyma provides a mechanism for the enhanced parenchymal toxicity to PFP we’ve previously reported [21-23]. From the data presented, we conclude that the HMOX1 and SOD1 mRNA and protein upregulation are suitable oxidative stress detection markers to measure effects of PFP exposure.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Cell populations are location-specific and have unique functions within the lung. The inability of neonates to upregulate antioxidants in the parenchyma provides a mechanism for the enhanced parenchymal toxicity to PFP we’ve previously reported [21-23]. From the data presented, we conclude that the HMOX1 and SOD1 mRNA and protein upregulation are suitable oxidative stress detection markers to measure effects of PFP exposure.…”
Section: Discussionmentioning
confidence: 52%
“…We have previously shown that animals exposed to PFPs have increased cellular toxicity. Further, following exposure there are age-dependent and lung compartmental changes in levels of non-enzymatic (GSH, GSSG) and enzymatic (GCL, GSR, GPX, GSTs) antioxidants [21-23]. …”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that HEMA leads to induction of AhR-dependent xenobiotic-metabolizing enzymes, followed by metabolism of HEMA to a reactive metabolite, which induces apoptosis. Chan et al (2013) reported transcript expression of CYP1A1 and CYP1B1 in the neonatal (7 days old) and adult (8 weeks old) male Sprague-Dawley rat lung. CYP1A1 and CYP1B1 mRNA were higher in the adult compared with the neonatal rat lung (CYP1A1 mRNA more than 250-fold).…”
Section: Cyp and Cyp Reductase Transcript Expressionmentioning
confidence: 99%
“…Abdull Razis et al (2011) observed increases of the CYP1A1 and 1B1 protein upon treatment of rat lung precision-cut slices with the glucosinolates glucoraphanin or glucoerucin. Chan et al (2013) reported protein expression of CYP1A1 and CYP1B1 in the neonatal and adult rat lung. CYP1A1 protein was increased by particulate matter ("PM") using an ultrafine premixed flame particle ("PFP") as a defined and replicable agent.…”
Section: Expression Of Cyp and Related Proteinsmentioning
confidence: 99%
“…The occupational setting is now considered as the most likely exposure route to engineered nanoparticles, but medical formulations may result in a wider population exposure [12]. The contribution of exposure to ultrafine particles such as those from combustion processes, to respiratory and skin diseases as well as more insidious and complex pathologies such as cancer and cardiovascular dysfunction, is now becoming apparent [93][94][95]. Their cumulative effects, or more likely the knock-on effect to neighbouring cells as well as more distant tissues and organs (i.e., paracrine signalling and cell activation) plays a key role in their toxicity at the systemic level.…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 99%